Allopregnanolone (3α-Hydroxy-5α-pregnan-20-one) derivatives with a polar chain in position 16α: Synthesis and activity - Slavíková, Barbora (2009)
The lipophilic nature of allopregnanolone prevents its user-friendly application in human medicine. On inspiration by pReviously prepared allopregnanolone with a 16α -bound tetraethylammonium salt, an attempt was made to produce allopregnanolone analogues with polar groups introduced into position 16α with the goal of increasing water solubility, brain accessibility, and potency of neuroactive steroids. The Michael addition to derivatives of pregn-16-en-20-one was the key reaction step. The link between the steroid skeleton and the new side chain was either a methylene group (when diethyl malonate was added) or an oxygen atom (when a hydroxy derivative was added). [35S]TBPS displacement was used to evaluate the products. Several carbamates (but not their parent alcohols) displaced TBPS from the picrotoxin binding site on GABAA receptors. Although none of them was more potent than the above ammonium salt, which stimulated this study, their nonionic nature should not prevent their passage into the brain. © 2009 American Chemical Society.